2022
DOI: 10.23736/s0022-4707.22.13567-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lower-limb muscular and tendon mechanical properties and strength on countermovement jump performance

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In a recent study, Men et al [23] applied an intervention program twice a week for 12 weeks to U9 soccer pla observing improvement in CMJ at 6 and 12 weeks compared with the initial measurem It is known that the stretch-shortening cycle affects jump performance [14,21] the improvement observed in SJ and CMJ in this study may be attributed to the impa the INT program on the efficiency of the stretch-shortening cycle of the participants Previous studies have also reported that SJ performance depends on concentric con tion [30], the myotatic reflex, and the ability of muscle fibers to store elastic energy du the stretch-shortening cycle [31]. Furthermore, improvement in intermuscular and i muscular coordination and tendon stiffness are factors that can influence jump pe mance [32,33].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In a recent study, Men et al [23] applied an intervention program twice a week for 12 weeks to U9 soccer pla observing improvement in CMJ at 6 and 12 weeks compared with the initial measurem It is known that the stretch-shortening cycle affects jump performance [14,21] the improvement observed in SJ and CMJ in this study may be attributed to the impa the INT program on the efficiency of the stretch-shortening cycle of the participants Previous studies have also reported that SJ performance depends on concentric con tion [30], the myotatic reflex, and the ability of muscle fibers to store elastic energy du the stretch-shortening cycle [31]. Furthermore, improvement in intermuscular and i muscular coordination and tendon stiffness are factors that can influence jump pe mance [32,33].…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have also reported that SJ performance depends on concentric contraction [30], the myotatic reflex, and the ability of muscle fibers to store elastic energy during the stretchshortening cycle [31]. Furthermore, improvement in intermuscular and intramuscular coordination and tendon stiffness are factors that can influence jump performance [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…That fore there is an urgent need for more studies using this methodology. According to most recent publication by Wdowski et al (2022), higher countermovement jump performance is enabled by higher elasticity (smaller decrement value), stiffness, and tone, with smaller creep-ability and quicker stress-relaxation times measured from Achilleus tendon. Two latter parameters are unique to newest myotonometric device.…”
Section: Discussionmentioning
confidence: 99%
“…According to most recent observations, the elasticity of the muscles in master athletes is lower than in sedentary coevals (Gervazi et al, 2017) and intensive physical exercise significantly increases stiffness in the Achilles tendon (Pozarowszczyk et al, 2017). Most recent work correlations strongly Achilles tendon elasticity (among other parameters) to countermovement jump height (Wdowski et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…during soccer training/match play. Furthermore, a stiffer tendon is associated with a faster rate of torque development ( Bojsen-Møller et al, 2005 ), which is also linked to greater lower-limb strength and power outputs ( Bojsen-Møller et al, 2005 ; Wdowski et al, 2022 ). Thus, strength training could have multiple benefits for soccer players, with changes in tendon properties likely due to the cumulative remodeling that occurs after each bout of exercise.…”
Section: Introductionmentioning
confidence: 99%